File 2768/1913 'Arms traffic: Muscat warehouse; claims of British firms - Laubenburg, C H; Darlow, W; Elbaz, Abraham; Goguyer, Antoine (British Library, 1911)
This file contains letters relating to the sale and shipment of arms and ammunition to Muscat in Oman. The majority of the correspondence is between the British firm of C H Laubenburg and British Political Agent in Muscat. The letters discuss changes to particular shipments of arms and ammunition as well as disputes and claims on payments due to the arms supplier. Other firms included in the correspondence are that of a W Darlow of Bedford, and Kynoch Limited. French correspondence in the file is issued from the French Consul in Muscat, Antoine Goguyer or Algerian Merchant Abraham Elbaz.
Keywords: Relations -- Oman -- Royaume-Uni